PROYEK MEDIA PEMBELAJARAN MATEMATIKA BERBASIS AUGMENTED REALITY BERBANTUAN ASSEMBLR EDU BAGI GURU SD - Wibowo, Sigit; Surayanah, Surayanah; Yuniawatika, Yuniawatika; Syawaludin, Ahmad; Listiawan, Danang; Al Farizza, Rifqi; Kurnia, Isnatul (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
The limited skills of teachers in developing digital learning media have become a critical issue in today’s rapidly evolving educational landscape. The Teacher Working Group (KKG) serves as a platform where teachers can share experiences, enhance competencies, develop innovative teaching methods and media, and participate in training to improve educational quality. Meanwhile, Augmented Reality (AR) holds great potential to enhance the quality of mathematics instruction. The purpose of this Community Service (PkM) activity was to provide elementary school teachers with knowledge and understanding of AR-based media and the Assemblr Edu application, as well as to improve their skills in developing digital learning tools. This program employed a participatory, training-based approach through socialization and project-based learning methods. Data were collected using observation, documentation, and questionnaires. The activity began with an introduction to the fundamental concepts of AR and Assemblr Edu, including key features and their application in educational settings. It was followed by intensive project-based training with ongoing mentoring, enabling teachers to produce final projects in the form of AR-based learning media. The effectiveness of the program was measured using five indicators evaluated on a Likert scale. The results indicated a substantial improvement in teachers' skills in developing AR-based learning media, with an average score rising from 52.83% before the training to 84.54% afterward—an increase of 31.71%. This improvement was supported by the high level of enthusiasm demonstrated by participants throughout the training sessions. Overall, the results demonstrate that the training was highly effective in enhancing teachers’ knowledge, technical abilities, and reflective capacity to integrate AR technology into a more interactive and meaningful teaching process.